Effectiveness of Leg Elevation to Prevent Spinal Anesthesia-Induced Hypotension during Cesarean Delivery in the Resource-Limited Area: Open Randomized Controlled Trial - Sofia Assen; Bedru Jemal; Adane Tesfaye (Anesthesiology Research and Practice)
Background. Postspinal hypotension is the most common complication after spinal anesthesia for cesarean section (CS). Hypotension mainly occurs due to the reductions of vascular tone leading to decreased systemic vascular resistance and decreased venous return. The aim of this study was to assess the effectiveness of leg elevation (LE) as a method of prevention of postspinal hypotension in patients who undergo cesarean section under spinal anesthesia. Methods. This is a single-center parallel-randomized controlled trial study, and 52 full-term parturients scheduled for elective cesarean section who meets inclusion criteria were included in the study. The randomization sequence was created by a researcher not participating in patient management using a computer random generator. The participant was randomly assigned to the leg elevation group (n = 26) or to the control group (n = 26) of usual perioperative care. Results. The proportions of patients who develop hypotension are lower (8 (33.3%)) in the leg elevation group than the control group (15 (62.5%)) with an X2 (1, N = 48) = 4.09, P=0.043. The relative risk of developing postspinal hypotension in the leg elevation group compared to the control group was 0.47 (95% CI, 0.28–1.00). The proportion of severe hypotension was significantly decreased in the leg elevation group at a P value of 0.02. Conclusion. Performing leg elevation immediately after spinal anesthesia reduced the incidence of hypotension. The trial is registered with PACTR201908713181850.